2021 IEEE World Haptics Conference (WHC) 2021
DOI: 10.1109/whc49131.2021.9517156
|View full text |Cite
|
Sign up to set email alerts
|

Comparing soft robotic affective touch to human and brush affective touch

Abstract: Affective touch is important for maintaining emotional bonds and providing comfort. In this pilot study, we developed a silicone pneumatic soft robotic haptic device (S-CAT) to provide affective touch and compared its performance with commonly used brush and human affective touch. The S-CAT device simulates the attributes of CToptimal affective touch in terms of velocity, temperature and force. In 22 participants we administered touch on their forearm from the S-CAT device (robot), a human hand and a soft brus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…In our study, we also invited participants to rate the pleasantness of the touch they received. Consistent with prior research (Ali et al, 2023;Pfabigan et al, 2023;van Hooijdonk et al, 2019;von Mohr et al, 2017;Zheng et al, 2021), our participants reported higher levels of pleasantness when the touch was administered at the CT-optimal speed and when delivered by a human rather than an artificial hand. Crucially, self-reports mirrored pupil results by revealing that participants reported the highest ratings of pleasantness when tactile stimulation featured both CT-optimal speed and human contact simultaneously.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we also invited participants to rate the pleasantness of the touch they received. Consistent with prior research (Ali et al, 2023;Pfabigan et al, 2023;van Hooijdonk et al, 2019;von Mohr et al, 2017;Zheng et al, 2021), our participants reported higher levels of pleasantness when the touch was administered at the CT-optimal speed and when delivered by a human rather than an artificial hand. Crucially, self-reports mirrored pupil results by revealing that participants reported the highest ratings of pleasantness when tactile stimulation featured both CT-optimal speed and human contact simultaneously.…”
Section: Discussionsupporting
confidence: 89%
“…Haptic devices simulate attributes of human affective touch, such as gentle stroking, which has been shown to produce pleasant sensation,15 relieve psychological distress16 and reduce the sense of social isolation associated with being apart from caregivers 17–19. However, such tactile interventions have not been widely explored as a tool to reduce procedural anxiety in radiotherapy patients.…”
Section: Introductionmentioning
confidence: 99%
“…Feedback mode was manipulated by the provision of visual-only versus visuotactile emoticons. The visual component was identical between the conditions but the tactile component of the visuotactile feedback was delivered via a wearable sleeve which can deliver affective touch at CT-optimal speeds (6cm/sec) and whose properties and effects have been described and validated in a separate study (S-CAT; [77]; see details below). To add variance to the kind of visual feedback participants received, we chose 6 emoticons per valence which are typically used to convey socially supportive meanings at different intensities.…”
Section: Main Aims Design and Data Analysismentioning
confidence: 99%